Bibliography on Cold Regions Science and Technology. Volume 35, Part 1 - Thuronyi, Geza T. (1981)
The Bibliography on Cold Regions Science and Technology was first published in 1951 and is a continuing publication of the Cold Regions Bibliography Project in the Science and Technology Division of the Library of Congress. It is sponsored by and prepared for the Cold Regions Research and Engineering Laboratory. Volumes 1-15 were issued as the Bibliography on Snow, Ice and Permafrost, SIPRE Report 12. Beginning with volume 16 the designation was changed to CRREL Report 12. With volume 20 the title was changed to Bibliography on Snow, Ice and Frozen Ground, with Abstracts, and with volume 23 the current title was adopted. The present volume contains material accessioned between October 1980 and September 1981. It contains the full citation of 4341 items, in many cases with abstracts. Pt. 2 is an index section divided into author and subject indexes. See also Volume 35, Part 2, ADA115955.